Consultants as Knowledge Brokers: Issues and Implications for China Tourism Research. Issue 1 (2nd January 2017) - Xiao, Honggen; Liu, Zhaoping; Cheng, Christopher
ABSTRACT: Consultants play a unique role as knowledge brokers in a scientific community. In the accelerating demand for knowledge-based practices, consulting has not only turned into a flourishing profession, it has also served as an effective strategy for academics to demonstrate practical implications of their work through spreading innovative ideas and promoting the use of knowledge for industry, policy and development practices. As a result, consulting has become an area of research in its own right in such fields as business and management, information and technology, and health studies or healthcare. In tourism, nonetheless, research on consultancy as knowledge brokering has been particularly limited. This article presents a general review and critique on consulting as knowledge brokering, and highlights issues, perspectives and implications for future research on this subject in the potentially largest origin and destination in world tourism.